Evidence of a s-wave subdominant order parameter in YBa2Cu3O7-d from break-junction tunneling spectra - Akimenko, A.I.; Bobba, F.; Giubileo, F.; Gudimenko, V.A.; Piano, S.; Cucolo, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The tunneling spectra of YBa2Cu3O7–δ break-junctions have been investigated for the tunneling direction close to the node one. The behavior of the zero-bias conductance peak (ZBCP) and Josephson current have been studied with temperature and magnetic field. The observed deep splitting of ZBCP which starts at TS < 20–30 K is in agreement with the theory for the dx2–y2 ± is order parameter [Y. Tanuma, Y. Tanaka, and S. Kashiwaya,Phys. Rev. B64, 214519 (2001)]. We also observed that a low (0.04 T) magnetic field significantly depresses such splitting. The 1/ T temperature dependence of maximum Josephson current that goes to saturation at T<TS also confirms the mixed order parameter formation.